SILICON TUBE FRONTALIS SUSPENSION IN SIMPLE CONGENITAL BLEPHAROPTOSIS - Ali, Zulfiquar; Kazmi, Hasan Sajid; Saleem, Muhammad Khalid bin; Shah, Ashfaq Ali (Journal of Ayub Medical College Abbottabad, 2011)
Background: Ptosis is an abnormally low position of the upper eyelid. Congenital ptosis should be corrected in early years of childhood. The aim of this study was to assess the efficacy and complications of frontalis suspension using silicon tube for simple congenital blepharoptosis with poor levator function. Methods: A prospective study was performed on 33 children who underwent frontalis suspension using silicon tube from Jan 2008 to Jun 2011 with a minimum of 6 month follow-up. Functional success was defined when 3 criteria were met: (a) satisfactory lid height defined as marginto-reflex distance ‰¥3.5 mm with minimal frontalis action (brow up); (b) satisfactory lid symmetry (‰¤2 mm asymmetry in margin-to-reflex distance) between two lids; and (c) satisfactory cosmesis, i.e., normal lid contours. Results: The mean follow-up duration was 9 months (range 6.5-27 months). The functional success rate was 91.4% (32/35 eyes). Three eyes had complications. In one eye (2.8%), recurrence of ptosis due to slippage of knot was seen, one eye developed infection of tract, and one with bilateral ptosis developed abnormal tenting of one of the lid. Conclusion: In simple congenital ptosis with poor levator function, frontalis suspension using silicon tube has good efficacy and an excellent safety profile. The results of frontalis suspension using silicon tube are comparable to fascia lata and superior to other non-autogenous materials. Keywords: Frontalis sling, brow suspension, congenital ptosis